2004
DOI: 10.1111/j.1600-0463.2004.apm1120206.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thyroidectomy on the histology of rat sublingual gland

Abstract: This study was carried out to investigate the effect of thyroidectomy on the histology of rat sublingual gland. Twenty-eight male Wistar albino rats, aged 4 weeks and weighing between 45-55 g, were used. The rats were divided into two experimental groups (control and thyroidectomy), each containing 14 animals. Total thyroidectomy of rats was performed under ether anesthesia in thyroidectomy group. The rats in the control group were sham operated without having the thyroidectomy. Seven rats randomly selected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Also in hypothyroid rats acini were widely separated [31] . This was clarified by Oncu et al (2004) [24] who observed atrophy of acini and Hayat et al (2010) who declared an increase in the amount of inter acinar & interlobular connective tissue in hypothyroidism [13,24] . Intense vacuolation was observed in semithin sections of hypothyroid glands but mild vacuolation was observed in hyperthyroid rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also in hypothyroid rats acini were widely separated [31] . This was clarified by Oncu et al (2004) [24] who observed atrophy of acini and Hayat et al (2010) who declared an increase in the amount of inter acinar & interlobular connective tissue in hypothyroidism [13,24] . Intense vacuolation was observed in semithin sections of hypothyroid glands but mild vacuolation was observed in hyperthyroid rats.…”
Section: Discussionmentioning
confidence: 99%
“…Sections were stained with Haematoxylin and Eosin (H & E) for routine histological study. Toluidine blue staining technique was used for the mast cells examination [24] . Sections were examined with the light microscope and photographed with the Lecia ICC50 W camera.…”
Section: Histological Studymentioning
confidence: 99%
“…It is well established that the cholinergic system is involved in higher brain functions such as learning and memory. Some authors' results demonstrated that T4 and DON administered in combination resulted in more effective restoration levels of ACh and synaptic proteins than either alone [14,19,45,46] Oxidative stress is an imbalance between the production of oxidizing agents and antioxidant activity of defence systems. Mitochondria are the core cell organelle that uses oxygen to produce energy.…”
Section: Discussionmentioning
confidence: 99%
“…The parathyroids were preserved and received post operative treatment. The sham group (euthyroid animals) underwent the same procedure without thyroid removal [19] .…”
Section: The Operation (Thyroidectomy)mentioning
confidence: 99%
“…It is defined as a condition when the level of the thyroid hormones decreases below the normal need of the body [2]. The hypothyroidism is a complex hormonal dysfunction rather than a single hormonal defect [3]. Thyroid hormone is a powerful modulator of cardiac function [4].…”
Section: Introductionmentioning
confidence: 99%